Protein profiling of Hevb1 and Hevb3 in Hevea species obtained from the 1995 germplasm collection - Nurul Faziha I.,; Shamsul Bahri A.R.,; Suhaizan L.,; Iffah Hazirah M.N.,; Ngadin A.A., (Penerbit Universiti Kebangsaan Malaysia, 2017)
Most of commercial latex products originated from natural rubber produced by Hevea brasiliensis. Hevea latex contained of rubber particles that are linked with numerous allergens protein. The allergens protein associates with rubber particles can cause allergic reaction that range from contact and systemic urticarial to asthma, anaplyaxis and even death. Although allergen proteins are well known to be involved in rubber synthesis of H. brasiliensis, their presence in this species as well as other Hevea species is still need to be determined. For sustainability production of high demanding commercial latex, this study is conducted to investigate the protein profiling of two allergens on eight Hevea species obtained from the 1995 germplasm collection. Latex collected from eight Hevea species were prepared to detect allergens protein of Hevb1 and Hevb3 using SDS Polyacrylamide Gel (SDS-PAGE). Immunoblotting technique was used to evaluate compatibility of allergens protein to bind with monoclonal and polyclonal antisera. The results showed that both of Hevb1 and Hevb3 proteins were detected in eight Hevea species. However, Hevb1 and Hevb3 proteins showed different ability in binding the monoclonal and polyclonal antisera. Data on protein profiling of eight Hevea species constitute a potential source of good trait in future plant breeding or as a key to have a future rubber tree with less or allergen free latex.